Impact of COVID‐19 in pediatric oncology care in Latin America during the first year of the pandemic. Issue 10 (20th May 2022) - Villanueva, Gabriela; Sampor, Claudia; Palma, Julia; Villarroel, Milena; Valencia, Diana; Lombardi, Mercedes García; Garcia, Wendy Gomez; Caceres, Eva Lezcano; Sobrero, Victoria; Garcia, Lilia; Cabrera, Victor; Maza, Ivan; et al.
Abstract: Background: The ongoing coronavirus 2019 disease (COVID‐19) pandemic strained medical systems worldwide. We report on the impact on pediatric oncology care in Latin American (LATAM) during its first year. Method: Four cross‐sectional surveys were electronically distributed among pediatric onco‐hematologists in April/June/October 2020, and April/2021 through the Latin American Society of Pediatric Oncology (SLAOP) email list and St Jude Global regional partners. Results: Four hundred fifty‐three pediatric onco‐hematologists from 20 countries responded to the first survey, with subsequent surveys response rates above 85%. More than 95% of participants reported that treatment continued without interruption for new and active ongoing patients, though with disruptions in treatment availability. During the first three surveys, respondents reported suspensions of outpatient procedures (54.2%), a decrease in oncologic surgeries (43.6%), radiotherapy (28.4%), stem cell transplants (SCT) (69.3%), and surveillance consultations (81.2%). Logistic regression analysis showed that at the beginning of the first wave, participants from countries with healthcare expenditure below 7% were more likely to report a decrease in outpatient procedures (odds ratio [OR]: 1.84, 95% CI: 1.19–2.8), surgeries (OR: 3, 95% CI: 1.9–4.6) and radiotherapy (OR: 6, 95% CI: 3.5–10.4). Suspension of surveillance consultations was higher in countries with COVID‐19 case fatality rates above 2% (OR: 3, 95% CI: 1.4–6.2) and SCT suspensions in countries with COVID‐19 incidence rate above 100 cases per 100, 000 (OR: 3.48, 95% CI: 1.6–7.45). Paradoxically, at the beginning of the second wave with COVID‐19 cases rising exponentially, most participants reported improvements in cancer services availability. Conclusion: Our data show the medium‐term collateral effects of the pandemic on pediatric oncology care in LATAM, which might help delineate oncology care delivery amid current and future challenges posed by the pandemic.